tHE FATTY ACID SPECTRUM OF TUMOR TISSUE IN CERVICAL CANCER WITH DIFFERENT HISTOPATHOLOGIC GRADES - B. S. Khyshiktuev; E. V. Kayukova; V. A. Kayukov; P. P. Tereshkov (Сибирский онкологический журнал)
The higher fatty acid spectrum of tumor tissue in cervical cancer with different histopathologic grades was studied using the method of gas-liquid chromatography. Irrespective of differentiation grade, the high level of saturated fatty acids as compared to the control was observed mainly due to the increase in the amount of С14:0 and  occurrence of С19:0. The increased level of monounsaturated fatty acids was observed in tumor tissue as compared to the control samples. Deficiency of ω-6 polyunsaturated fatty acids was noted in all tissue fragments. The specific features of fatty-acid composition of cervical cancer with different differentiation grade were found.